2010
DOI: 10.1007/s11894-009-0079-2
|View full text |Cite
|
Sign up to set email alerts
|

Latest and Emerging Therapies for Primary Biliary Cirrhosis and Primary Sclerosing Cholangitis

Abstract: Primary biliary cirrhosis (PBC) and primary sclerosing cholangitis (PSC) are the two most common causes of chronic cholestatic liver disease in adults. In PBC, therapy with ursodeoxycholic acid (UDCA) is safe and has been associated with tangible biochemical, histologic, and survival benefits. However, a need for different or adjuvant therapies remains for specific subsets of PBC patients, including those who do not respond to UDCA and those who have advanced histologic disease at presentation. Similarly, bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 81 publications
1
24
0
Order By: Relevance
“…Chronic cholestasis causes liver fibrosis, cirrhosis, liver failure, hepatocellular carcinoma, and cholangiocarcinoma. Primary biliary cholangitis (PBC) and primary sclerosing cholangitis (PSC) are two common types of progressive chronic cholestasis diagnosed in humans [48, 49]. The etiologies of PBC and PSC are not fully clear but involve genetic, immune, and environmental factors.…”
Section: Bile Acids As Therapeutic Agentsmentioning
confidence: 99%
“…Chronic cholestasis causes liver fibrosis, cirrhosis, liver failure, hepatocellular carcinoma, and cholangiocarcinoma. Primary biliary cholangitis (PBC) and primary sclerosing cholangitis (PSC) are two common types of progressive chronic cholestasis diagnosed in humans [48, 49]. The etiologies of PBC and PSC are not fully clear but involve genetic, immune, and environmental factors.…”
Section: Bile Acids As Therapeutic Agentsmentioning
confidence: 99%
“…This study revealed an elaborate regulatory cascade, tightly controlled by SHP, for regulating both the maintenance of bile acid production and detoxification in the liver [59]. A better understanding of these mechanisms may aid the development of better agents to decrease serum bile acids in chronic cholestatic liver diseases such as primary biliary cirrhosis and sclerosing cholangitis [144, 145]. …”
Section: Shp In Metabolismmentioning
confidence: 99%
“…Alternative therapies, including combinations of UDCA with immunomodulating drugs, have been tried but have not been successful according to limited clinical trials 4. Thus, there is an urgent need to develop alternative beneficial treatments for these chronic cholestatic diseases 5, 6…”
mentioning
confidence: 99%